Antenatal depression and its predictors among HIV positive women in Sub-Saharan Africa; a systematic review and meta-analysis - Abebe, Gossa Fetene; Alie, Melsew Setegn; Adugna, Amanuel; Asemelash, Daniel; Tesfaye, Tamirat; Girma, Desalegn; Asres, Abyot (Frontiers in Psychiatry, 2024)
Background: Antenatal depression in Human Immunodeficiency Virus (HIV) positive pregnant women can have significant adverse effects on both the mother and newborns, yet it is often over looked in pregnancy care in Sub-Saharan Africa (SSA). Despite this, there is limited data on the combined prevalence of antenatal depression and its predictors among HIV-positive women in the region.Objective: To assess the pooled prevalence of antenatal depression and its associated factors among HIV-positive women in SSA.Methods: All primary cross-sectional studies published before 1 st January/2024, were included.We conducted searches in relevant databases; PubMed, HINARI, Web of Science, PsycINFO, Psychiatry Online, ScienceDirect, and Google Scholar. The Joanna Briggs Institute checklist was used to critically appraise the selected studies. To assess heterogeneity among the studies, we utilized the I 2 test. Publication bias was evaluated using a funnel plot and Egger's test. The forest plot was used to present the combined proportion of antenatal depression and odds ratio, along with a 95% confidence interval.The pooled prevalence of antenatal depression among HIV-positive women in Sub-Sah aran Africa was found to be 30.6% (95% CI, 19.8%-41.3%). Factors significantly associated wit h antenatal depression among HIV-positive women in SSA included being unmarried (AOR: 3.0 9, 95% CI: 1.57 -6.07), having a previous history of depression (AOR: 2.97, 95% CI: 1.79 -4.9 1), experiencing intimate partner violence (IPV) (AOR: 2.11, 95% CI: 1.44 -3.09), and experien cing stigma (AOR: 1.36, 95% CI: 1.05 -1.76).: High prevalence of antenatal depression among HIV-positive women in SSA under scores the need for prioritizing identification and management. Interventions addressing factors 3 like IPV and stigma, along with training for healthcare providers in recognizing symptoms and providing support, are recommended.